Advocacy - McPeake, Robert (Bar manuals, 2012)
Advocacy provides a highly practical introduction to the skills and techniques required to deliver submissions and applications in the courts. It covers the full range of courtroom transactions from opening and closing cases, to conducting examination-in-chief, cross-examination, and questioning witnesses